Seed, hide and seek: Echoes of Presence - Šimurdová, Magdaléna (Vysoké učení technické v Brně. Fakulta výtvarných umění, 2025)
Tato diplomová práce prostřednictvím prostorové instalace zkoumá fragment imaginativního posthuman světa, v němž se organické a civilizační materiály propojují v nové formy nonhuman entit. Instalace tematizuje ambivalenci života – napětí mezi křehkostí a vitální silou – a rozvíjí otázky materiální agence, vztahovosti a rozostřování binárních struktur. Nonhuman entity nejsou chápány jako reprezentace, ale jako aktivní aktéři environmentu, který je vnímán jako otevřené pole mezi bytím, procesem a vnímáním. Práce vychází z principů nového materialismu a posthumanistického myšlení, které rozšiřují rámec subjektivity za hranice lidského.

This diploma thesis explores a fragment of an imaginative posthuman world through a spatial installation in which organic and civilisational materials intertwine to form new types of nonhuman entities. The installation explores the ambivalence of life - the tension between fragility and vital force - and develops questions of material agency, relationality and the dissolving of the boundaries of binary structures. Nonhuman entities are not conceived as representations, but as active agents within an environment perceived as an open field between being, process, and perception. The work is grounded in the principles of new materialism and posthumanist thought, which expand the framework of subjectivity beyond the boundaries of the human.
Seed, hide and seek: Echoes of Presence
Keywords: nový materialismus; nonhuman turn; mezidruhová ekologie; posthumanismus; entity; environment; prostorová instalace; objekt; materiál; new materialism; nonhuman turn; interspecies ecology; posthumanism; entities; environment; spatial installation; object; material